2021
DOI: 10.1111/acfi.12904
|View full text |Cite
|
Sign up to set email alerts
|

Attracting accounting and finance graduate talent – beyond the Big Four

Abstract: This study responds to ongoing challenges with recruiting quality graduate talent in the accounting/finance industry, critical given transforming labour market requirements. Drawing on Person‐Organisation Fit (POF) theory, we explore what attracts 475 Accounting/Finance students to graduate roles, their preferences for different organisation types, and influences on career decision‐making. Supporting earlier work, we evidence dominating preferences for ‘Big Four’ firms yet discern several appealing features of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…It does, however, challenge recent studies of university students’ career values where job security was classified as an extrinsic factor (Jackson and Tomlinson 2019). The favouring of intrinsic values among accounting students aligns with Jackson et al.’s (2022) study yet contravenes earlier work where they rated extrinsic values more highly (e.g., Schoenfeld et al. 2017, p. 117).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…It does, however, challenge recent studies of university students’ career values where job security was classified as an extrinsic factor (Jackson and Tomlinson 2019). The favouring of intrinsic values among accounting students aligns with Jackson et al.’s (2022) study yet contravenes earlier work where they rated extrinsic values more highly (e.g., Schoenfeld et al. 2017, p. 117).…”
Section: Discussionsupporting
confidence: 82%
“…The findings relating to remuneration (reported in RQ1) notwithstanding, and echoing Deloitte (2016Deloitte ( , 2018, we found that having a positive workplace culture, opportunities for vicarious and continuous learning, professional fulfilment and work-life balance were the most important factors influencing ECAs to apply for a given role. Assuming that ECAs have, by definition, some (albeit limited) work experience, this finding suggests that whereas they may prioritise employer brand image and working for a Big Four firm as students (Jackson et al 2022) and new graduates (Gillezeau and Fowler 2019), their values change over time as they accrue more work experience, consistent with SCCT. Career advancement was also found to be an important job attractor for ECAs, observed by Jackson et al (2023) as being closely associated with perceptions of career success among early career accountants.…”
Section: Discussionmentioning
confidence: 85%
“…The findings support the view that employer branding is an antecedent to retention (Bharadwaj et al ., 2022) and can influence the candidate's choice of employer via POF assessment (Huang, 2022; Tanwar and Kumar, 2019). There is also support for the view that the recruitment process also plays a role in establishing POF (Jackson et al ., 2022) as a reflection of the work environment. “Starting Salary and Benefits” also continue to be a consideration for graduates when evaluating the attractiveness of an employer (Zaharee et al ., 2018).…”
Section: Discussionmentioning
confidence: 70%
“…The management of the onboarding process has also been shown to impact the decision-making process for candidates on whether to accept or reject a job offer from the organisation (Yamamura et al ., 2010). This highlights how applicants establish their POF via the recruitment process, drawing on intrinsic and extrinsic factors as they seek career sustainability, leading to a competitive advantage for the employer (Jackson et al ., 2022).…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
“…Nevertheless, when considering the potential benefits of BT in the auditing context, it is essential to analyze how the size of the audit firm may affect the perceived advantages of BT for the external auditor's role. Institutional differences exist between big four and non-big four audit firms, including firm size, global reach, market share, client base and financial capital (Afsay et al ., 2023; Jackson et al ., 2022). These institutional differences may lead to differences in the perceptions of the benefits of BT between large-sized and small and medium-sized audit firms (Afsay et al ., 2023).…”
Section: Literature Reviewmentioning
confidence: 99%